2021
DOI: 10.7554/elife.70597
|View full text |Cite
|
Sign up to set email alerts
|

PGFinder, a novel analysis pipeline for the consistent, reproducible, and high-resolution structural analysis of bacterial peptidoglycans

Abstract: Many software solutions are available for proteomics and glycomics studies, but none are ideal for the structural analysis of peptidoglycan (PG), the essential and major component of bacterial cell envelopes. It icomprises glycan chains and peptide stems, both containing unusual amino acids and sugars. This has forced the field to rely on manual analysis approaches, which are time-consuming, labour-intensive, and prone to error. The lack of automated tools has hampered the ability to perform high-throughput an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…The method for purification of PG sacculi has remained relatively unchanged since the 1960s ( 33 ), while similarly the method for compositional analysis based on reverse-phase high-performance liquid chromatography (HPLC) has remained the standard protocol since it was first developed by Glauner in the 1980s ( 34 ). However, recently the application of newer technologies to enhance and streamline the analysis methodology has been proposed and advanced ( 25 , 35 38 ). Our previous study demonstrated the application of MS feature extraction coupled with a bioinformatic methodology proved to be useful in examining the composition of the PG from P. aeruginosa at a level of detail not seen using other methodologies ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The method for purification of PG sacculi has remained relatively unchanged since the 1960s ( 33 ), while similarly the method for compositional analysis based on reverse-phase high-performance liquid chromatography (HPLC) has remained the standard protocol since it was first developed by Glauner in the 1980s ( 34 ). However, recently the application of newer technologies to enhance and streamline the analysis methodology has been proposed and advanced ( 25 , 35 38 ). Our previous study demonstrated the application of MS feature extraction coupled with a bioinformatic methodology proved to be useful in examining the composition of the PG from P. aeruginosa at a level of detail not seen using other methodologies ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated the application of MS feature extraction coupled with a bioinformatic methodology proved to be useful in examining the composition of the PG from P. aeruginosa at a level of detail not seen using other methodologies ( 25 ). Patel et al ( 38 ) recently developed a novel piece of software, PGfinder, which is a robust, open-access platform for the automated annotation of muropeptides. The comparison of the muropeptide annotations from our previous study aligned well with the annotation performed by Patel et al using PGfinder ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current knowledge about the bacterial PG chemical structure has been mainly obtained by analytical methods proposed by Glauner et al more than 30 years ago (Glauner et al, 1988), which involves: purification of the mature PG sacculus, removal of proteins covalently linked to the PG, digestion with muramidase (i.e., lysozyme) to generate soluble disaccharide peptides (muropeptides) and separation of the muropeptides by liquid chromatography (LC) (Alvarez et al, 2016; Desmarais et al, 2013). These analyses have significantly improved during the last decade thanks to the use of a more advanced ultra-performance liquid chromatography (UPLC) technology replacing high pressure liquid chromatography (HPLC) systems, and the use of in-line LC-mass spectrometry (MS) systems for PG analysis (Alvarez et al, 2016; Bern et al, 2017; Desmarais et al, 2013; Kuhner et al, 2014; Patel et al, 2021). Additionally, the PG isolation protocol has also been simplified and accelerated by replacing the use of the ultra-centrifuge by bench centrifuges, and the reduction or removal of detergents used during sacculi isolation (Alvarez et al, 2016; Kuhner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%